PERISTIWA MASUKNYA KUMAN M. LEPRAE SECARA IMUNOLOGI DAN TROYAN HORSE FENOMENA - JULIYANTI . (JURNAL ILMIAH KOHESI, 2023)
The immune response to most organisms consists of 2 components, cellular and humoral. M. Leprae and the pattern of clinical manifestations shown by leprosy patients are highly dependent on human genes which may be related to several chromosomal regions, such as chromosomes 6q25, 10p13, 17q11-q21, 20p12. Cell-mediated immunity is mediated by lymphocytes which are processed during fetal life by the thymus and are called T lymphocytes or T cells. Mycobacterium leprae may enter the body through the nose and then spread to the skin and nerves via the circulation and the Trojan horse phenomenon occurs. A mechanism for M. Leprae to escape the attack of the first layer of the immune system by riding in monocytes as in the infection is tuberculosis in the lungs, and being carried into deeper organs while multiplying. Human toll-like receptor macrophage activation also up-regulates the expression of vitamin D receptors and the vitamin D-1-hydroxylase gene, leading to triggering of antimicrobial cathelicidin peptides and intracellular M. tuberculosis eradication. Many factors play a role when the germs that cause leprosy enter the human body, apart from a person's immune system, genetic factors, the pathogenicity of the germs themselves.